2005
DOI: 10.1111/j.0008-4085.2005.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Trade and direct investment in producer services and the domestic market for expertise

Abstract: Foreign producer services can provide substantial benefits for domestic firms. We build on earlier monopolistic-competition models of intermediate producer services in this paper. Results show that: (1) while foreign services are partial-equilibrium substitutes for domestic skilled labour, they may be general-equilibrium complements, (2) service trade can provide crucial missing inputs that reverse comparative advantage in final goods, (3) the 'optimal' tax on imported services may be a subsidy, and (4) in our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(75 citation statements)
references
References 13 publications
3
70
1
1
Order By: Relevance
“…ICT could optimize producer service trade structure through reducing technology gap in order to realize manufacturing upgrading. Research has also shown that when a country increases its producer service trade to compensate for the shortage of domestic final products, it generates an externality by introducing technology advancements (Markusen 1989;Markusen, et al 2005;Francois 1990;Arnold et al 2008;Amit and Konings 2007). Yang also found that the OECD countries often utilize imported producer services to enhance the development of the industries that they have traditional enjoyed comparative advantages (Yang 2015).…”
Section: Logistics Globalizationmentioning
confidence: 99%
“…ICT could optimize producer service trade structure through reducing technology gap in order to realize manufacturing upgrading. Research has also shown that when a country increases its producer service trade to compensate for the shortage of domestic final products, it generates an externality by introducing technology advancements (Markusen 1989;Markusen, et al 2005;Francois 1990;Arnold et al 2008;Amit and Konings 2007). Yang also found that the OECD countries often utilize imported producer services to enhance the development of the industries that they have traditional enjoyed comparative advantages (Yang 2015).…”
Section: Logistics Globalizationmentioning
confidence: 99%
“…Increasing concerns with the validity of linear ways of thinking about the innovative process represent a call to go beyond this traditional, shallow view of economic evolution. Dedicated research must also tackle softer forms of innovation generation and facilitation, as well as the development of forward and backward linkages among organizations (Markusen, Rutherford, & Tarr, 2005).…”
Section: Knowledge-intensive Business Servicesmentioning
confidence: 99%
“…This paper builds on the work of Markusen, Rutherford and Tarr (2005), Jensen, Rutherford and Tarr (2007) and Balistreri, Rutherford and Tarr (2008). Markusen, Rutherford and Tarr developed a stylized model where foreign direct investment is required for entry of new multinational competitors in services, but they did not apply this model to the data of an actual economy.…”
mentioning
confidence: 91%